Saadi and the modern discourse of Iran - عیسی امن خانی; منا علی مددی (تاریخ ادبیات, 2011)
Aside from the aesthetic aspect of Saadi's works, which has caused him to be referred to as a master, Iranians for many centuries accepted this poet as their moral and wisdom teacher. This acceptance continued until the years of the constitutional revolution, until with the beginning of these era-making years, the teachings presented by Saadi were criticized by some intellectuals and orientalists such as Edward Brown, and were considered to be in conflict with modern teachings. In this article, the authors try to examine this issue once again using Foucault's discourse theory. Therefore, based on the aforementioned theory, they have first tried to find the dominant presupposition of each discourse - "inequality" in the discourse of the Saadi era and "equality" in the discourse of the constitutional era - to find out the reasons for their conflict and then to show that the formation of Saadi’s thinking in the pre-modern discourse, which is based on the premise of inequality, has caused signs of inequality to be reflected in Saadi's teachings. The critics and intellectuals of the constitutional era - whose default was equality - did not like this issue and they criticized and denied Saadi and his teachings. Interestingly, they were not right in their denial either.